SOCIAL BIOETHICS DURING THE COVID-19 PANDEMIC: USE OR REMOVE MASKS AFTER VACCINATION? - Argota-Pérez, George (2021)
The aim of the study was to describe social bioethics during the COVID-19 pandemic and their use or removal of masks after vaccination. Th e study was carried out in August 2021 where 97 people (45 men and 52 women) residing in the cities of Ica, Puno and Tacna (Peru) were selected through an intentional non-probabilistic sampling and for which they showed a second vaccine dose administered against COVID-19. Four age class intervals were established: I) 45-50, II) 51-55, III) 56-60, and IV) 61-65; these were diff erentiated by sex and in which they were asked the following: “If you are vaccinated, do you think you should use the mask? Yes __ No __”. “Do you wear a double mask on public roads or in public spaces? Yes __ No __”. “Do you frequently eat food in public places with your family? Yes __ No __”. Likewise, the relationship between wearing and removing the mask by sex was as follows: men (yes = 24; no = 21), women (yes = 35; no = 17) where in both sexes it was indicated that wearing the mask is the preference. The proportion for both sexes was: men = 1.1 and women = 2.1. It is concluded that the action of being vaccinated does not argue to remove the mask and thus it was observed from the greater preference of its use as a means of protection in men and women from 45 to 65 years old, which showed social bioethics for the care of human health.